Characterization and identification of the most appropriate nonionic surfactant for enhanced oil recovery - Shilpi Sarmah; Subrata Borgohain Gogoi; Fan Xianfeng; Annanya A. Baruah (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract The paper focuses on the behaviour of nonionic surfactants (NISs) for enhanced oil recovery (EOR) processes with special reference to its applicability in the reservoirs of Upper Assam. The present work specifically studies three NISs, viz. Tergitol 15-s-7(Tg7), Tergitol 15-s-9 (Tg9) and Triton X 405(TX), based on their surface tension (ST), dynamic interfacial tension, hydrophilic–lipophilic balance, emulsion stability, aqueous stability, particle size analysis and phase behaviour. Simultaneously, crude oil from an oil field of upper Assam Basin was characterized based on API gravity, kinematic and dynamic viscosities, pour point and acid number. Core flood studies were conducted in the reservoir core to determine the recovery of crude oil during secondary water flood and EOR by NISs. It was observed that Tergitol 15-S-7 when mixed with Triton X-405 (Tg7TX) had the least interfacial tension (IFT) as compared to individual NIS and their mixtures. The recovery was found to be as high as 25.67% after secondary water flood from the original oil in place when Tg7TX followed by chase water was used as an exotic fluid for EOR. This work is an attempt to identify NISs mixtures for EOR for Upper Assam Basin.